Detection of HLA-B*57:01 by real-time PCR: implementation into routine clinical practice and additional validation data. (February 2014) - Russo, Cinzia Dello; Lisi, Lucia; Fabbiani, Massimiliano; Gagliardi, Dimitri; Fanti, Iuri; Giambenedetto, Simona Di; Cauda, Roberto; Navarra, Pierluigi
Aim: HLA-B*57:01 status needs to be determined before initiating abacavir therapy. We developed a pharmacogenetic real-time (Q)-PCR screening test using two sets of sequence specific primers. This test has been implemented into routine clinical practice.Materials & methods: HIV-infected patients admitted at our University Hospital were thus genotyped using the above mentioned test. A panel of 80 DNA samples with a known genotype were used to characterize Q-PCR conditions using different master mixes.Results: A total of 353 patients were genotyped, detecting 15 (4.25%) HLA-B*57:01 positive carriers. Among the negative patients, 17.2% were treated with abacavir without any hypersensitivity reaction. Using different Q-PCR master mixes, significantly lower cutoff Ct values were found, thus new analytical settings are provided.Conclusion: The pharmacogenetic test developed in our laboratory for the fast screening of HLA-B*57:01 can be successfully implemented into routine clinical practice. All 16 sequences (including an additional six) currently known for the HLA-B*57:01 allele are detected by sequence specific primers used in this test. The Brilliant II SYBR ® Green QPCR MM (Stratagene) can safely replace the master mix originally used to develop the test. Original submitted 2 August 2013; Revision submitted 2 December 2013